Ответ:
Объяснение:
125(5a⁻³b³)⁻²a⁻²b⁴=5³⁻²a⁶⁻²b⁻⁶⁺⁴=5a⁴/b²=5·0,2/(0,5)²=1/0,5²=1/0,25=100/25=4
(0,5a⁻²)⁻²÷(32a⁵b²)³=a⁴⁻⁵/(0,5²·32³b⁶)=1/(0,5²·(4³)³ab⁶)=1/(0,5²·4⁹·(0,5)⁻⁴·0,25⁶)=1/(0,5²⁻⁴·4⁹·(0,5²)⁶)=1/(0,5⁻²⁺¹²·4⁹)=1/((1/2)¹⁰·(2²)⁹)=1/2⁻¹⁰⁺¹⁸=1/2⁸=1/4⁴=1/16²=1/256
(2³a⁻³b)⁻¹·64a⁻⁴÷a⁻⁵=2⁻³·(2³)²a³⁻⁴⁺⁵/b=2⁻³⁺⁶a⁴/b=8a⁴/b=8·(-0,125)⁴/0,5=8·(1/8)⁴/0,5=1/(8³·0,5)=2·2⁹=2¹⁰=4⁵=1024
27·(-3²a³)÷(3⁵a⁻¹b⁻²)³=-3³⁺²⁻¹⁵a³⁺³b⁶=-3⁻¹⁰a⁶b⁶=-(ab)⁶/3¹⁰=-(-0.1·0,1)⁶/3¹⁰=-0,01⁶/3¹⁰
(√97 +2)²= √97² + 2·2·√97 +2²=97 +4√97 +4 = 101 +4√97
Квадрат кончается на 625, значит возводили в квадрат число с 25 на конце.
a(a+50)=50000
a=200
число равно 225.
можно так найти число а такое что а*(а+1)=506
506=2*253=2*11*23
220+5=225
2x²<span>-9x+4=0
D=(-9)</span>²-4*2*4=81-32=49=7²
x1=(9+7)/4=4
x1=(9-7)/4=1/2=0.5